Administration of deep sea shark liver oil reduce malondialdehid (mda) levels on male wistar rats exposed to cigarette smoke - Feily Sari Moelyono; Wimpie Pangkahila (Fakultas Kedokteran Universitas Udayana, 2018)
Introduction: The Deep Sea Shark Liver Oil contains squalene, omega-3, and beta-carotene that could act as effective antioxidant to counter oxidative stress caused by cigarette smoke. This study aims are to prove the effect of Deep Sea Shark Liver Oil on reducing MDA levels in male Wistar rats exposed to cigarette smoke. Methods: This study was a pre and post-test control group experimental study. 20 male Wistar rats were used and divided into 2 groups that were exposed to cigarette smoke for 45 minutes once a day. Group 1 received placebo while group 2 received 140 mg Deep Sea Shark Liver Oil per 200 grams of rat body weight for 14 days. Result: The pre-test MDA level in both groups were comparable and normally distributed (Group 1: 7.71±0.23 nmol/ml; Group 2: 7.57±0.28 nmol/ml). However, post-test result showed that the MDA level in treatment group was significantly lower compared to control (Group 1: 8.45±0.37 nmol/ml; Group 2: 6.34±0.33 nmol/ml; p: <0.05). Conclusion: In conclusion, the administration of 140 mg of Deep Sea Shark Liver Oil per 200 grams of rat body weight for 14 days effectively reduced MDA levels in rats exposed to cigarette smoke.